유아의 실행기능이 단어형 미래계획기억 과제와 범주형 미래계획기억 과제 수행에 미치는 영향 - 박소연(So Yeon Park); 송하나(Hana Song) (Korean Journal of child studies, 2019)
Objective: This study aimed to investigate the influence of executive function on the development of prospective memory in young children. Methods: The participants of this study included 47 preschool children aged 4 and 5 years. Children completed word- and category-based tasks that measured prospective memory. The following tasks were also used to assess executive function in children: Flanker, Day/Night, Backward Digit Span, and Dimensional Change Card Sort tasks. Results: The inhibitory control and working memory of children significantly predicted prospective memory measured by the word-based task. Inhibition particularly accounted for prospective memory in the category-based task. Conclusion: The findings demonstrated the influence of the components of executive function on the prospective memory of young children in the preoperational period. KCI Citation Count: 0